Patients' perceptions of physical activity before and after joint replacement: a systematic review with meta-ethnographic analysis. Issue 1079 (25th August 2015) - Smith, Toby O; Latham, Sarah; Maskrey, Vivienne; Blyth, Annie
ABSTRACT: Background: It has been perceived that people following total hip arthroplasty (THA) or total knee arthroplasty (TKA) have the capability, with reduced pain, to increase their levels of physical activity. Objectives: To determine the attitudes and perceptions of people awaiting or having undergone THA or TKA to physical activity post-arthroplasty and to identify potential facilitators or barriers to engage in active living and physical activity pursuits. Methods: Systematic review of published and unpublished databases was undertaken from their inception to November 2014. Studies exploring the attitudes and perceptions of people awaiting or having undergone THA or TKA to physical activity post-arthroplasty were included. Data were analysed through a meta-ethnography approach. Results: From 528 citations, 13 papers were eligible, sampling 282 people post-THA or TKA. The literature was judged moderate to high quality. Following THA and TKA, people either wished to return to their pre-pathology level of physical activity or simply be able to engage in less physically demanding activities that are meaningful to them and their lifestyles. Barriers to engaging in higher levels of physical activity were largely related to limited information, which culminated in fear surrounding 'doing the right thing' both for individual's recovery and the longevity of the joint replacement. Conclusions: While many people post-THA or TKA wish to return to pre-pathological physical activity status, there is limited interest in actually undertaking greater levels of physical activity post-arthroplasty either for pleasure or health gains. Improvement in education and awareness of this may be key drivers to improve habitualisation of physical activity post-arthroplasty. Trial registration number: CRD42014014995.